Portraying Teacher Performance Management in Schools Implementing Semester Credit System - Mardianti, Desi; Bambang Budi Wiyono; Ali Imron; Ery Tri Djatmika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The purpose of this study is to reveal the management of teacher performance management in schools that implement the Semester Credit System (SKS). This study uses a qualitative approach with a multi-site study design, using in-depth interviews, observation, and study of documents in collecting data. Data analysis was carried out in stages. The results showed that teacher performance planning in schools that manage the SKS program includes planning for the needs of the SKS program (needs for materials, facilities, infrastructure, and program facilities as well as the program implementing team), learning planning in the SKS program, planning for placement in the SKS class, planning for mentoring and academic guidance, training planning, capacity building, and budget planning for the SKS program. Second, the implementation of teacher performance is carried out by (a) preparing the needs of the SKS program by forming a team for developing the SKS program curriculum and making SKS program guidelines. The team is chaired by the principal, the waka of the curriculum as program coordinator, and teachers as team members. The team is tasked with preparing program guides, providing academic advisors, creating curriculum structures, determining learning loads, and recommending the number of credits to students. (b) academic tests, psychology, grades V and VI report cards, UN scores for consideration. Placing students in the SKS class in the first semester and determining the SKS program students in the second semester. Provide KRS. (c) Provide academic services in the form of academic guidance, teachers become academic advisors, provide study plan cards (KRS), help students determine credits, make learning tools, analyze student development, and socialize the development of student learning outcomes. (d) making lesson plans, making other teaching tools through the MGMP forum, preparing teaching materials, teaching processes, and teaching assessments. Third, teacher performance evaluation is carried out by the principal on an ongoing basis. Evaluation is carried out through meetings (meetings), briefings, and supervision. Supervision using a format that already exists and is available at school.